The impact of the hypoxia‐VEGF‐vascular permeability on COVID‐19‐infected patients. Issue 2 (30th October 2021) - Cao, Yihai
Abstract: Effective treatment of patients with severe COVID‐19 to reduce mortality remains one of the most challenging medical issues in controlling unpredictable emergencies caused by the global pandemics. Unfortunately, such effective therapies are not available at this time of writing. In this article, I discuss the possibility of repurposing clinically available anti‐VEGF (vascular endothelial growth factor) drugs that are routinely used in oncology and ophthalmology areas for effective treatment of patients with severe and critical COVID‐19. Our preliminary findings from a clinical trial support the therapeutic concept of using anti‐VEGF for treating patients with severe COVID‐19 to reduce mortality. The aim of this article is to further provide mechanistic insights into the role of VEGF in causing pathological changes during COVID‐19 infection. Abstract : Leaking plasma from blood vessels triggered by COVID‐19 infection plays a crucial role in causing pulmonary atelectasis (lung collapse), which fills up the lung air sacs with liquid and the lung becomes deflated. If sufficiently large areas of the lung tissue become deflated by this problem, the lung tissue can no longer take enough air and oxygen for the entire body and patients suffer from life‐threatening shortness of breath. This article discusses the possibility of repurposing clinically available drugs designed for treating cancer and eye diseases for the benefit of treating patients with severe COVID‐19 by blocking vascular leakage.